Bangladesh Development Update, April 2021 : Moving Forward - Connectivity and Logistics to Strengthen Competitiveness - Haven, Bernard James; Beyer, Robert Carl Michael; Dihel, Nora Carina; Arshad, Selvia; Shahriar, Shegufta (World Bank, Dhaka, 2021)
This report provides an assessment of the state of the economy in Bangladesh, discussing the outlook, risks, and key reform challenges. It covers: real sector developments, focusing on growth and its components; inflation; monetary and financial sector developments; external sector trends, focusing on the balance of payments, foreign exchange reserves and the exchange rate; and fiscal outcomes, focusing on revenue mobilization, public expenditures, and deficit financing. The special focus section of this update discusses how improved connectivity and logistics can help the Bangladeshi economy recover from the Coronavirus (COVID-19) pandemic and build resilience to future shocks.